AKUNTANSI PERSPEKTIF USAHA MIKRO KECIL MENENGAH (SURVEI PADA UMKM DI KOTA MATARAM) - Bq. Anggun Hilendri; Sapto Hendri BS; L. Takdir Jumaidi; D. Tialurra Della Nabila (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
Accounting information has an important role to achieve business success, including for small businesses. Accounting information can be a reliable basis for decision-making in managing small businesses, including market development decisions, pricing and others. The purpose of this study was to determine the perspectives of MSMEs owners about the accounting and financial management of their businesses. Based on the research results, perspective accounting MSMEs owners in the Mataram city is limited by income record and expenditure only or simple bookkkeeping. Financial management is done simply by knowing the initial capital has returned and the remaining results of operations are profit Keywords: accounting, financial management